The Use of Podcast to Improve Students’ Speaking Competency of Tenth Grade Students of SMA Negeri 1 Amlapura in Academic Year 2015/2016 - Daniati, A S; Mardjohan, Asril; Piscayanti, K S (Universitas Pendidikan Ganesha, 2016)
The objective of this research was to improve students’ English speaking competency by using podcast in teaching and learning. This research was conducted in SMA Negeri 1 Amlapura, as the subject of the research was the tenth grade students of SMA Negeri 1 Amlapura, i.e. X MIA 1 class. The object of research was English speaking competency of X MIA 1 students. The method used in this study was Classroom Action Research minimum score. It can be concluded that the English competency of the X MIA 1 students could be improved by using podcast in English teaching and learning. In addition, the result of the questionnaire and observation in the classroom showed that the students were more motivated to learn by using podcast.